Pengaruh orientasi pasar, orientasi kewirausahaan terhadap kinerja pemasaran UMKM batik di Kabupaten Jombang - Yahya Reka Wirawan (Universitas PGRI Madiun, 2017)
This study aims to determine the effect of market orientation and entrepreneurial orientation toward marketing performance partially or simultaneously. The population in this study are traders batik SMEs in Jombang district and samples taken 94 respondents obtained by the calculation formula Slovin. The sampling technique used was purposive random sampling. Methods of analysis, linear regression analysis using SPSS 22.0. The results of this study with regression analysis of Y = 0.131 + 0,510X2 0,436X1 + + e. Partial test results show the market orientation and entrepreneurial orientation have a significant effect on the performance marketing. The test results simultaneously obtained Fhitung =55.478 with a significance of 0.000 < 0.05. The coefficient of determination (Adjusted R2) of0.54, in that it can be interpreted that unplanned purchases described by the retail service and the atmosphere in the store by 54%, while the remaining 46% is explained by other variables not examined in this study. Conclusions from this research is the higher market orientation and entrepreneurial orientation, the higher the level of performance marketing. Suggestions for merchants batik SMEs in Jombang district for more attention to what is in demand by consumers. As well as more courageous in taking risks to bring new fashions.